2000
DOI: 10.1111/j.1526-4610.2000.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hypotension: The Nonspecific Nature of MRI Findings

Abstract: We present three patients who complained of postural headache related to different types of intracranial hypotension: spontaneous or primary, and secondary, but presenting the same findings on brain magnetic resonance imaging. Diffuse pachymeningeal gadolinium enhancement supports the belief that the enhancement is a nonspecific meningeal reaction to low pressure.Abbreviations: ICH intracranial hypotension, SPICH spontaneous or primary intracranial hypotension, SIH secondary intracranial hypotension, PPH postl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Many characteristic MR findings have been associated with IH regardless of its etiology. [1][2][3][4][5][6][7][8][9][10][11][12] On review of the MR imaging of patients presenting to our institution with IH, we have identified a highly reliable novel imaging sign for the diagnosis of IH. We have termed this sign the "venous distension sign" (VDS) and evaluated for it on routine nonenhanced sagittal T1-weighted imaging of the brain.…”
mentioning
confidence: 99%
“…Many characteristic MR findings have been associated with IH regardless of its etiology. [1][2][3][4][5][6][7][8][9][10][11][12] On review of the MR imaging of patients presenting to our institution with IH, we have identified a highly reliable novel imaging sign for the diagnosis of IH. We have termed this sign the "venous distension sign" (VDS) and evaluated for it on routine nonenhanced sagittal T1-weighted imaging of the brain.…”
mentioning
confidence: 99%
“…1e, f). At a 1-year follow-up examination, she was free from PDPH symptoms.Imaging findings of severe PDPH may be similar to those of spontaneous intracranial hypotension, including PMGE, engorgement of the venous system, CSF accumulation, and subdural hematoma, as revealed by both cranial and spinal MRI [1][2][3]. In this case, despite resolution of the clinical symptoms, active CSF leakage was revealed by CT myelography and the opening pressure of CSF upon lumbar puncture was normal on day 15.…”
mentioning
confidence: 93%
“…Nonetheless, symptoms of ICH may be caused any time the duramater is traumatized, such as after diagnostic LP, myelography, spinal anesthesia, spinal injury, and spinal surgery (6,20,33), craniotomy or placement of a ventriculoperitoneal shunt (18). Systemic diseases such as dehydration, diabetic coma, uremia and, hyperpnea are the other medical causes of ICH (8).…”
Section: Introductionmentioning
confidence: 99%